Intrapreneurial Factors Influencing Organizational Citizenship Behaviour in Mobile Brigade Corps - Hidayat, Syamsul; Meria, Lista; Purwohedi, Unggul; Safariningsih, Ratna Tri Hari; Kosasih, Fajar Gumilang; Budiarti, Sari (Pandawan, 2026)
The Mobile Brigade Corps of the Indonesian National Police carries strategic responsibilities that require personnel to demonstrate strong organizational citizenship behaviour supported by intrapreneurial attributes. Intrapreneurial factors within public security institutions are increasingly important to enhance adaptability innovation and sustainable organizational performance in line with the Sustainable Development Goals particularly SDGs 8 on decent work and SDGs 16 on strong institutions. This study aims to examine the influence of intrapreneurial related factors namely perceived organizational support empowering leadership and proactive personality on organizational citizenship behaviour with leader member exchange as a mediating variable. A quantitative approach was employed using a survey of 8020 Mobile Brigade Corps personnel with 367 respondents selected through simple random sampling. Data were analyzed using Structural Equation Modeling with AMOS version 24. The results indicate that perceived organizational support empowering leadership and proactive personality significantly influence organizational citizenship behaviour both directly and indirectly through leader member exchange. The mediating role of leader member exchange strengthens the relationship between intrapreneurial factors and extra role behaviour. The findings highlight the importance of fostering an intrapreneurial environment within public security organizations to promote voluntary and proactive employee behaviour. This study contributes to organizational development strategies that support institutional effectiveness sustainability and the achievement of SDGs oriented governance.